A Prospective Observational Study of Medication Reconciliation at Admission, Transfer and Discharge to Reduce Medication Discrepancies in Inpatient - Devani, Hiren Rasikbhai; Patel, Charmiben Sunilbhai; Modi, Mansi Chetan (Journal of Pharmacy Practice and Community Medicine)
Background: Medication reconciliation is the method in which patient’s medication orders were compared to all the medications that the patient has been taking. This Reconciliation process for circumvent the medication discrepancies such as omission, drug interaction, duplications, or any medication related errors. Medication reconciliation ensures standard treatment for patients and also avoid harm from medicines is reduced. It is the baseline from which drug treatment is continued on admission, therapeutic interventions are made, and self-caring will be continued on discharge. Objectives: The primary objective of this study was to assess the prevalence and types of medication discrepancies found during medication reconciliation. The secondary objective was to determine the impact of medication reconciliation and to examine the potential severity of medication discrepancies also to find out drug’s involvement in medication errors. Methodology: A prospective, observational study of medication reconciliation was done for 3 months in the inpatient department of the hospital. Results: A total 120 patients were included in this study, out of which 67(55.83%) were, male and 53(44.17%) were female. We found discrepancies in 45(37.50%) patients. Discrepancies were found at different transition points-At admission 34(57.36%) discrepancies identified, at transfer 4(6.78%) discrepancies identified, and at discharge 21(35.59%) discrepancies identified. Conclusion: Medication reconciliation process has a highly latent to recognize clinically important discrepancies for all patients. Medication reconciliation requires more focus in hospitals along with requirement for clinical pharmacy department for the medication safety.
Keywords: Medication reconciliation; Patient safety; Transitions of care; Medication discrepancies; Medication Error